Quality Evaluation of Rice Treated by High Hydrostatic Pressure and Atmospheric Pressure Plasma - Ji Hae Lee; Koan Sik Woo; Cheorun Jo; Heon Sang Jeong; Seuk Ki Lee; Byong Won Lee; Yu-Young Lee; Byoungkyu Lee; Hyun-Joo Kim (Journal of Food Quality)
This study applied high hydrostatic pressure (HHP) and atmospheric pressure plasma (APP) treatments to rice and examined the effects of the treatments on the microbial contamination and physicochemical properties. The microbial population was 100% sterilized by HHP and reduced by up to 34% by APP. Color a values were increased by up to 285% and 33% in HHP and APP, respectively. HHP increased fructose (∼8,256%) but decreased glucose, sucrose, and maltose (∼97%, −100%, and −93%, respectively). APP only mildly modified sugar composition compared with HHP. Retrogradation factors were not changed remarkably by HHP or APP. In conclusion, HHP sterilized microorganisms, but the sterilization was accompanied by high modifications to color and sugar composition. APP had a lesser effect on the microbial population, but it only mildly changed the physicochemical properties of the rice. Therefore, application of either HHP or APP could be considered depending on the intended use of the rice.